Triple receiver public key encryption cryptosystem - Liutao ZHAO; Lin ZHONG; Jidong LIU; Caiqun WANG; Dan WU (网络与信息安全学报)
A triple receiver public key cryptosystem was proposed.In the cryptosystem,a sender encrypted a message and sent to three receivers,while the three receivers were able to decrypt the message with their own private keys.Based on bilinear map,two triple receiver public key encryption schemes with different security were constructed.If the gap bilinear Diffie-Hellman (GBDH) problem and the computational Diffie-Hellman (CDH) problem were proved formally to be intractable,then the two schemes proposed were semantically secure against chosen-plaintext attacks and against adaptive chosen ciphertext attacks respectively.The proposed scheme only added an exponential operation and a hash operation,and constructed three independent receivers which had a high efficiency.Analyses show that proposed scheme can improve the security of TLS protocol and apply to hierarchical public key cryptosystems.